KOMUNIKASI PEMASARAN RUMAH SUTERA ALAM BOGOR DALAM UPAYA MENINGKATKAN JUMLAH PENGUNJUNG - Amarilisya Zetira; Diana Amaliasari; Imani Satriani (UNIVERSITAS PAKUAN, 2019)
ABSTRACT Writing this reports aims to find out how marketing communications activities carried out by Rumah Sutera Alam in an attempt to increase the number of visits as well as to find out what factors become advocates and brominated in carrying out the activities of marketing communications at Rumah Sutera Alam. This research uses qualitative research approaches that produce descriptive data in the form of the written word and methods, the data used are the primary data and secondary data. Engineering data collection in the study include interviews, observations, and documentation. The results of this study showed more to marketing communication activities that have been undertaken to increase the number of visitors from Rumah Sutera Alam in order to reach the target of visits that have been set. From the results of the research activities of the marketing communications it is important to be made by the company to introduce the offers products. Rumah Sutera Alam did marketing promotions through some promotional mix, such as personal selling, sales promotion, publicity, communication at the place of purchase, and internet marketing. There is a supporting factor in the implementation of marketing communications activities carried out by Rumah Sutera Alam, through internet marketing, publicity, communication of purchase, and the existence of reviews experiences of visitors through in Blog. While the factors restricting the existence of limitations the costs and human resources. Until now, Rumah Sutera Alam has not been able to maximize the entire elements of marketing communications activities.